M-Commerce and its impact on Today’s Economy - Hathi, Pradeep N. (Recent Research Reviews Journal, 2023)
Mobile commerce, often known as m-commerce, comprises the use of wireless portable devices such as mobile phones and tablets to undertake online commercial transactions such as the purchase and selling of items, banking on the internet, and bill payment. The main difference is that customers do not need a laptop or PC to achieve this. They can make use of portable technologies such as cell phones and tablets. Users can now use online shopping sites and other internet services from anywhere and at any time. For example, when someone purchases any products if they have an Android or iOS app, they are engaging in m-commerce. A mobile device may be used to buy and sell a variety of content assets such as games, programmes, ringtones, subscriptions, and so on. Mobile commerce offers organisations extraordinary market potential, high productivity, as well as elevated profitability due to intrinsic properties such as ubiquity, personalisation, flexibility, and diffusion.